BUILDING INTRUSION DETECTION SYSTEMS BASED ON THE BASIS OF METHODS OF INTELLECTUAL ANALYSIS OF DATA - Toliupa, Serhii; Brailovskyi, Mykola; Parkhomenko, Ivan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
Nowadays, with the rapid development of network technologies and with global informatization of society problems come to the fore ensuring a high level of information system security. With the increase in the number of computer security incidents, intrusion detection systems (IDS) started to be developed rapidly.Nowadays the intrusion detection systems usually represent software or hardware-software solutions, that automate the event control process, occurring in an information system or network, as well as independently analyze these events in search of signs of security problems. A modern approach to building intrusion detection systems is full of flaws and vulnerabilities, which allows, unfortunately, harmful influences successfully overcome information security systems. The application of methods for analyzing data makes it possible identification of previously unknown, non-trivial, practically useful and accessible interpretations of knowledge necessary for making decisions in various spheres of human activity. The combination of these methods along with an integrated decision support system makes it possible to build an effective system for detecting and counteracting attacks, which is confirmed by the results of imitation modeling.